Phosphoproteomic screening identifies physiological substrates of the CDKL5 kinase. (28th September 2018) - Muñoz, Ivan M; Morgan, Michael E; Peltier, Julien; Weiland, Florian; Gregorczyk, Mateusz; Brown, Fiona CM; Macartney, Thomas; Toth, Rachel; Trost, Matthias; Rouse, John
Abstract: Mutations in the gene encoding the protein kinase CDKL5 cause a debilitating neurodevelopmental disease termed CDKL5 disorder. The impact of these mutations on CDKL5 function is poorly understood because the substrates and cellular processes controlled by CDKL5 are unclear. Here, we describe a quantitative phosphoproteomic screening which identified MAP1S, CEP131 and DLG5—regulators of microtubule and centrosome function—as cellular substrates of CDKL5. Antibodies against MAP1S phospho‐Ser 900 and CEP131 phospho‐Ser 35 confirmed CDKL5‐dependent phosphorylation of these targets in human cells. The phospho‐acceptor serine residues in MAP1S, CEP131 and DLG5 lie in the motif RPXS A, although CDKL5 can tolerate residues other than Ala immediately C‐terminal to the phospho‐acceptor serine. We provide insight into the control of CDKL5 activity and show that pathogenic mutations in CDKL5 cause a major reduction in CDKL5 activity in vitro and in cells. These data reveal the first cellular substrates of CDKL5, which may represent important biomarkers in the diagnosis and treatment of CDKL5 disorder, and illuminate the functions of this poorly characterized kinase. Synopsis: CDKL5 kinase is mutated in a neurodevelopmental disease termed CDKL5 disorder but the cellular targets and functions of CDKL5 are unclear. A phosphoproteomic screen to identify cellular targets of CDKL5 now addresses this gap. CDKL5 phosphorylates MAP1S, CEP131, and DLG5, proteins involved in regulation of microtubules and centrosomes. In all three substrates, the phosphorylated serine lies in an RPXSA motif, with in vitro analysis showing certain amino acids other than Ala also tolerated C‐terminal to the phosphoacceptor serine. CDKL5 activity is controlled by tyrosine auto‐phosphorylation in its T‐loop. Pathogenic CDKL5 mutations cause severe reduction in kinase activity towards MAP1S and CEP131 in cells and in vitro . Abstract : Identification of phosphorylation targets reveals a sequence preference for the neurodevelopmental disease‐linked CDKL5, and that pathogenic mutations decrease activity towards microtubule‐ and centrosome‐associated substrates.